SECONDARY DEFORMITIES OF DENTITIONS IN RESIDENTS OF THE KHARKIV REGION - Slynko, Y.O.; Sokolova, I.I.; Garmash, O.V. (World of Medicine and Biology, 2025)
The study was devoted to analyzing the prevalence and types of secondary deformities associated with the presence of partial dentition defects among residents of the Kharkiv region. The results of the digital panoramic radiography analysis confirm a high prevalence of dentition defects among residents of the Kharkiv region – averaging 53.7 % – and demonstrate a direct correlation with the patients’ age. A significant increase in the prevalence of partial dentition defects is observed in the 25–29 age group, where the prevalence exceeds 40 %, and it remains high in the oldest age group (75–84 years).
Keywords: partial dentition defects; secondary adentia; secondary deformities of dentition; X-ray examination; digital panoramic radiography; age-related prevalence; gender-related prevalence